Introduction: The politics of the list. (February 2016) - de Goede, Marieke; Leander, Anna; Sullivan, Gavin
This articles introduces the special issue on 'The Politics of the List.' We observe that lists proliferate as a technique of governance across multiple domains, including health, security, and commerce. We argue that it is important to take seriously the form and technique of the list itself and engage the knowledge practices, governance effects and ways of ordering the world that the list format enables. In other words, the special issue seeks to 'remain in the register of the list, ' to unpack its technological arrangements and juridical power. This introduction sets out the key themes of this special issue, through discussing, in turn, the list as a technology of knowledge, the list as a technique of law and governance, the list's complex relation to space and the relation between the list and the digital. We draw on these four elements to characterise what we call the politics of the list in an era of complexity.